MEMBANGUN MINAT STEM MELALUI PELATIHAN ROBOTIKA SEDERHANA DI SD KANISIUS BEJI, PLAYEN GUNUNG KIDUL - Siswoyo, Agus; Arianto, Eko; Novyanto, Antonius Hendro (LPPM Universitas Bina Bangsa, 2024)
Simple robotics training at SD Kanisius Beji, Playen, Gunung Kidul, was carried out as an effort to build students' interest in STEM (Science, Technology, Engineering, and Mathematics) learning. The lack of exposure of students to technology and engineering is the background to the importance of this activity. The community service method used includes direct training in assembling and programming simple robots, involving students in grades IV to VI. The results of the training showed an increase in students' interest and understanding of STEM concepts, with 85% of students successfully completing the task of assembling the robot independently. This activity also improved students' critical and collaborative thinking skills. In conclusion, this simple robotics training is effective in introducing students to the basics of STEM and has the potential to be applied more widely in the elementary education curriculum